Effectiveness of Emergency Ligation of Internal ILIAC Artery in Controlling Post-Partum Hemorrhage - Humaira Bashir, Sabeeha Khan, Rubina Baber, Rehana Taskeen, Iram Rafique, Durri Shahwar (Pakistan Journal of Medical & Health Sciences, 2022)
Treatment of severe pelvic bleeding remains a major challenge in obstetrics and Gynecology. In this situation, an attempt was made with variable success at bilateral internal iliac artery ligation (BIAL). Aim: The purpose of this study was to evaluate the effectiveness of this procedure in females with intractable pelvic hemorrhage. Methods: This observational study was conducted at the Department of Obstetrics and Gynecology of Mufti Mehmood Teaching Hospital D I Khan for one year duration from January 2021 to December 2021. During the study period, a total of 35 emergency internal iliac arteries ligation and, if necessary, gradual uterine de-vascularization or cesarean hysterectomy were performed as a life-saving procedure. Results: Haemotasis was successfully achieved in 33 patients. Of the 35 patients who required a cesarean hysterectomy, two patients died of multiple organ dysfunction following the hysterectomy. However, no complications related to BIAL were observed in any of the other patients. The mortality rate was 5.7% in this study. Conclusions: In our study, BIAL was recognized as a safe and effective treatment procedure for life-threatening obstetric haemorrhage. But for unknown reasons, the procedure is much less practiced than other radical options.